Analysis of the Biological Quality of Clean Water in the Male Dormitory - Yuliansari, Dini; Fatmalia, Enida; Wahyudin, Wahyudin (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
The use of unclean water is one of the causes of skin diseases. Skin diseases are often suffered by students in the Islamic boarding school environment because sanitation facilities may be inadequate. It is known that the water source in the Islamic boarding school uses drilled well water. The purpose of this study was to determine the quality of clean water in the male dormitory of the Abu Hurairah Mataram Islamic boarding school, which was reviewed biologically. This type of research is descriptive qualitative. The population in this study were all the water taps in the male dormitory of the Abu Hurairah Mataram Islamic boarding school. Based on the results of biological quality tests, including Coliform tests and Eschericia coli tests on water, it is known that the coliform test results obtained in sample A were 18 MPN / 100ml, sample B was 46 MPN / 100ml, sample C was 230 MPN / 100ml, and sample D was 0 MPN / 100ml and the results of Eschericia coli in sample A were 24000 MPN / 100ml, sample B was 24000 MPN / 100ml, sample C was 0 MPN / 100ml, and sample D was 0 MPN / 100ml. The water used by students still cannot be said to be suitable for use because of the presence of Escherichia coli and Coliform bacteria that can cause disease in humans. There needs to be treatment to reduce the bacterial content in sanitation facilities in Islamic boarding schools.